Evaluation of Aeroponic Minitubers of Newly Released Potato Varieties under Various Spacing Combinations - Sadawarti, Murlidhar J.; Buckseth, Tanuja; Singh, S. P.; Sharma, Ashwani Kumar; Kumar, Vinod; Singh, R. K.; Katare, Subhash; Singh, Brajesh; Samadhiya, R. K.; Singh, Y. P.; Sharma, S. K. (International Journal of Bio-resource and Stress Management, 2025)
This study was conducted during 2020–21 to 2023–24 at ICAR-Central Potato Research Institute, Regional Station, Gwalior, Madhya Pradesh, India to compare the production potential of newly released potato varieties grown as aeroponic minitubers under different spacing combinations under net house conditions. The planting was done in 2nd week of November each year two spacing combinations 30×10 cm2 (333333 plants ha-1) 30×15 cm2 (222222 plants ha-1) and four varieties viz Kufri Ganga-Medium maturing, Kufri Lima-Medium maturing heat tolerant and Kufri Mohan -early bulking medium maturing and Kufri Sangam-medium maturing processing with plot size of 1.80m2. The trial was planted in factorial RBD with three replications with spacing combinations as main plot and varieties as sub plots. The objective was to determine the optimal spacing for maximizing yield, tuber size, and overall performance of these varieties. No significant difference in growth parameters among spacing combinations, but varietal differences were observed. 30×10 cm2 spacing recorded significantly higher total tuber number (1571 thousand ha-1) compared to 30×15 cm2 spacing (1301 thousand ha-1). Varieties Kufri Ganga, Kufri Mohan, and Kufri Sangam recorded significantly higher total tuber numbers over Kufri Lima. Study suggests that newly released potato varieties grown as aeroponic minitubers should be multiplied at 30×10 cm2 spacing to achieve a higher number of tubers. Kufri Ganga and Kufri Mohan performed better in terms of total tuber weight, while Kufri Lima and Kufri Mohan had a higher percent of medium-sized tubers by number.